Ordnungsgemäß berufen, regiolokal leiten, mündiges Christsein fördern - Herbst, Michael 1955- (2017)
A vital church featuring a "mixed" economy of parishes and fresh expressions of church provides the basis for a pastoral vision less pressured by unrealistic demands on the minister and more related to volunteers.